Feasibility and Preliminary Effects of the BESMILE-HF Program on Chronic Heart Failure Patients: A Pilot Randomized Controlled Trial - Chen, Xiankun; Jiang, Wei; Olson, Thomas P.; Lundborg, Cecilia Stålsby; Wen, Zehuai; Lu, Weihui; Marrone, Gaetano (Frontiers in Cardiovascular Medicine, 2021)
Aims: The Baduanjin Eight-Silken-Movements wIth Self-Efficacy building for Heart Failure (BESMILE-HF) program is a contextually adapted cardiac rehabilitation program. It uses a traditional Chinese exercise, Baduanjin, to solve the unmet demand of exercise-based cardiac rehabilitation programs due to their scarcity and unaffordability in China. This pilot study assesses BESMILE-HF's feasibility and preliminary effects. Methods: Eighteen patients with chronic heart failure were included: 8 in a BESMILE-HF group (age: 67 ± 5 years, EF: 40.4 ± 13.6%) and 10 in a control group (age: 70 ± 13 years, EF: 42.9 ± 12.5%). Both received the usual medications, with the intervention group receiving additionally the BESMILE-HF program for 6 weeks. Feasibility was explored by participants' involvement in the intended intervention. Clinical outcome assessments were conducted at baseline and post-intervention, while adverse events were captured throughout the study period. Results: The BESMILE-HF program was well-received by patients, and adherence to the intervention was good. The intervention group completed all required home exercises and total home-practice time was correlated with baseline self-efficacy (r = 0.831, p = 0.011). Moreover, after 6 weeks, self-efficacy increased in the BESMILE-HF group (p = 0.028) and the change was higher than in the control [mean difference (MD): 3.2; 95% confidence interval (CI) 0.6–5.9, p = 0.004]. For the exercise capacity, the control group demonstrated a significant decline in peak oxygen consumption (p =0.018) whereas, the BESMILE-HF group maintained their exercise capacity (p = 0.063). Although the between-group difference was not statistically significance, there was clear clinical improvement in the BESMILE-HF group (1.5 mL/kg/min, 95% CI, −0.3 to 3.2 vs. minimal clinically important difference of 1 mL/kg/min). Throughout the study period, no adverse events related to the intervention were captured. Conclusions: BESMILE-HF is feasible for patients with chronic heart failure in Chinese settings. A larger sample size and a longer follow-up period is needed to confirm its benefit on clinical outcomes. Clinical Trial Registration:ClinicalTrials.gov: NCT03180320.